THE SOCIAL HOUSING AS A MECHANISM OF STATE SUPPORT FOR THE REALIZATION OF THE RIGHT TO HOUSING - Oliinyk, Nataliia; Samoliuk, Oleksandr (Public Management and Policy, 2025)
The article is devoted to the analysis of social housing as a mechanism of state support for the realization of citizens’ right to housing in Ukraine. Particular attention is paid to current state policies, legislative regulation of housing relations, implementation of social programs, and ensuring housing accessibility for vulnerable population groups. The study aims to identify key directions of state regulation and effective models for implementing the right to social housing under economic and social challenges, including the consequences of martial law. The research employed general scientific methods, including comparative and systemic analysis, analysis of legislation and normative acts, review of the practice of state programs, and synthesis of statistical data and contemporary studies by Ukrainian and foreign scholars. Data collection covered the analysis of legislative initiatives, implementation of experimental social housing programs, monitoring of the real estate market, and statistics on citizens’ housing provision. The study results indicate that the effective realization of the right to social housing requires a comprehensive approach combining legislative consolidation of social guarantees, state funding, support for municipal initiatives, and the introduction of innovative housing management models. It is established that state social housing programs contribute to increasing housing accessibility for low-income groups, ensuring social stability, and reducing the risks of housing insecurity. The integration of municipal and state approaches to social housing enhances the efficiency of resource allocation, ensures transparency in housing fund management, and optimizes the use of budgetary funds. The introduction of social programs targeting specific population groups and the integration of modern financial and economic mechanisms for implementing the right to housing contribute to promoting social justice, stability of the housing market, and the competitiveness of the national housing provision system.